1997
DOI: 10.1111/j.1438-8677.1997.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Biochemical, and Molecular Characters for the Taxonomy of the Subgenera of Scenedesmus (Chlorococcales, Chlorophyta)

Abstract: Biochemical and physiological properties of 16 Scenedesmus species representing the three subgenera Scenedesmus. Acutodesmus. and Desmodesmus are not suitable for species differentiation. All Scenedesmus species studied thus far produce secondary carotenoids, e.g. astaxanthin and canthaxanthin, under nitrogen-deficient conditions. In addition, with the exception of one strain, hydrogenase activity under anaerobic conditions is generally present. Sequence analyses of ribosomal 185 RNAs indicate that the subgenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…Especially, S. rubescens (formerly Chlorella fusca var. rubescens) (Kessler et al 1997) shows salt (NaCl) tolerance up to 3% NaCl (Huss et al 1999), but is not halophile. On the other hand, strain JPCC GA0024 was expected to have a halophilic behavior because the seawater requirement for efficient growth and lipid accumulation was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, S. rubescens (formerly Chlorella fusca var. rubescens) (Kessler et al 1997) shows salt (NaCl) tolerance up to 3% NaCl (Huss et al 1999), but is not halophile. On the other hand, strain JPCC GA0024 was expected to have a halophilic behavior because the seawater requirement for efficient growth and lipid accumulation was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of the 18S-rDNA gene clearly supported the designation of just two subgenera, Desmodesmus and Scenedesmus. The existing separation in the two subgenera Acutodesmus and Scenedesmus (Hegewald 1978) was not supported by this analysis and combined into one subgenus Scenedesmus (Kessler et al 1997). Subsequent sequence analysis of the more variable internal transcribed spacer 2 (ITS-2) region was used to further clarify the taxonomy of Scenedesmus .…”
mentioning
confidence: 90%
“…Kessler and co-workers using sequence analyses of 18S rDNA showed that two taxa of the unicellular Chlorella were in fact unicellular Scenedesmus while one Chlorella and one Kermatia had to be designated to Desmodesmus (Kessler et al 1997) ! A decade ago, an interesting dialogue took place between Trainor and Egan (1990) and Hegewald and Schmidt (1990) on Lagerheimia hindakii being the unicellular stage of D. subspicatus illustrative of the firmly anchored dogma of Desmodesmus and Scenedesmus being colonial.…”
Section: Morphological Variability Buoyancy and Unicellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For examp le, some researchers discussed the aforementioned characteristics in some cultured strains of D. communis (e.g., Ko marek & Ru zicka, 1969;Brezina, Hrib, & Ko marek, 1972;Steenbergen, 1978;Hegewald, 1989;Trainor, 1992;Bica et al, 2012). Kessler et al (1997) pointed out that the morphological characteristics and metabolic capacities are considered not only enough to clearly distinguish the different Scenedesmus and Desmodesmus taxa. Recently, the molecu lar phylogenetic analysis was imp lemented to solve some this taxonomic pu zzle (e.g., An, Friedl, & Hegewald, 1999;Van Hannen, Fin k, & Lurling, 2002;Hegewald & Wolf, 2003;Johnson, Fawley Vanormelingen et al, 2007;Fawley, M .W., Fawley, K.P.…”
Section: Introductionmentioning
confidence: 99%